IN PATIENTS WITH SUSPECTED CORD COMPRESSION, CAN DIRECT REQUEST FOR MRI IN THE EMERGENCY DEPARTMENT IMPROVE PATIENT SAFETY?. Issue 9 (14th August 2014) - Padfield, Emma; Hall, Sharon J; Keep, Jeff; Fleming, Graham
Abstract : Objectives & Background: To determine whether the Emergency Department (ED) could effectively identify patients with suspected cauda equina or cord compression who warranted further investigation with MRI, and thus request MRI without prior review from neurosurgeons. Methods: The ED proforma for management of patients with back pain was assessed with focus on the referral pathway from the ED to neurosurgeons (NS). Patients attending the ED during a 3 month period with a complaint of back pain and subsequent referral to the neurosurgeons were identified using the Symphony database. Electronic records and paper notes were used to assess the time between arrival in the ED and referral to neurosurgeons, and the time from referral to MRI. The MRI request and patient notes were used to assess the appropriateness of the referral. Results: 1055 patients attended with back pain during the three month period. 40 patients were referred to the neurosurgeons by an ED doctor. 34/40 were deemed to require an MRI by the neurosurgeons. In 4/6 who did not have an MRI the proforma had not been followed correctly. 1/6 did not have an MRI but was later found to have cauda equina when imaged as an outpatient. 1 patient was admitted under neurology. 7/34 had either cauda equina or severe canal stenosis requiring surgery. Median time to MRI from ED referral was 237 minutes with a wait time of 100 minutes for NS review prior to MRI. On 7 occasions when NS requested MRI without seeing the patient first, time to MRI was 108 minutes compared with 290 minutes if requested after review by NS. If MRI was requested by the ED it is estimated time to MRI could be reduced by 182 minutes. Conclusion: There was good correlation between ED and NS opinion on the need for MRI. Detection rate for cauda equina/severe stenosis (20.6%) was in keeping with other studies in the literature. There is significant time delay in the current referral process which can delay emergency treatment and may adversely affect patient outcome, and one patient was missed despite the proforma recommending MRI. ED doctors should request MRIs directly in the case of suspected cauda equina/cord compression .